Effects of Spirulina in Lead Induced Toxicities in Long Evans Rats - Rahman, MA; Moitry, NF; Alam, M; Yasmin, Z; Debnath, D; Mostofa, M (Journal of Environmental Science and Natural Resources, 2012)
The effect of spirulina in lead induce toxicity was conducted on 20 adult rats (Long Evans). Rats were randomly divided into four equal groups and subjected to treatments once daily for a period of 4 weeks. Rats treated with lead acetate showed severe toxic and significantly reduced erythrocytes count, hemoglobin content and significantly elevated SGPT, SGOT and ALP. Rats treated with lead acetate plus spirulina in two doses, 1500 mg/kg and 2000 mg/kg b.wt. were apparently normal. There hematological and biochemical parameters were not altered significantly. This experiment revealed that treatment with spirulina was effective in lead-induced toxicity and to restore altered values of hematological and biochemical parameters DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11557 J. Environ. Sci. & Natural Resources, 5(1): 79 - 82, 2012